2019
DOI: 10.5194/isprs-archives-xlii-2-w10-77-2019
|View full text |Cite
|
Sign up to set email alerts
|

COMPLEMENTARITY BETWEEN IN SITU STUDIES AND PHOTOGRAMMETRY: METHODOLOGICAL FEEDBACK FROM A ROMAN SHIPWRECK IN CAESAREA, ISRAEL

Abstract: <p><strong>Abstract.</strong> As a quick and effective way to archive the different stages of an excavation - notably to prepare the post-excavation phase and to document the production methods – photogrammetry has become an indispensable tool. Indeed, it offers a valid scientific model, usable by any member of the team and at any moment, without the need to return to the excavation site. Photogrammetry can also complement other archaeological tools such as manual surveys. The interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In [19] some methods for underwater documentation were presented and their advantages and disadvantages reported. Authors in [20] reported on the complementarity between in situ studies and photogrammetry by presenting the feedback from a roman shipwreck in Caesarea, Israel.…”
Section: Diver Based Data For Underwater 3d Reconstructionmentioning
confidence: 99%
“…In [19] some methods for underwater documentation were presented and their advantages and disadvantages reported. Authors in [20] reported on the complementarity between in situ studies and photogrammetry by presenting the feedback from a roman shipwreck in Caesarea, Israel.…”
Section: Diver Based Data For Underwater 3d Reconstructionmentioning
confidence: 99%